Oscillatory Line-driven Winds: The Role of Atmospheric Stratification - Joshua A. Key; Daniel Proga; Randall Dannen; Sterling Vivier; Tim Waters (The Astrophysical Journal, 2025)
Time-dependent numerical studies of line-driven winds using the Sobolev approximation have a history spanning over three decades. In many of these studies, the wind solutions display notorious oscillations. Two clues suggest the oscillations originate at the wind base: (i) simulations reach a steady state without oscillations when the base density is sufficiently low, and (ii) the oscillation dominant frequency is comparable to the Lamb cutoff frequency, ω _c , of acoustic waves propagating in a stratified hydrostatic atmosphere. Recently, Dannen et al. observed another clue: When the line force significantly weakens due to ionization, the winds become increasingly sensitive to the self-excited oscillations. Here, we present a set of simulations and perturbation analyses that further elucidate the source and characteristics of oscillations. We found that the line force adds wave energy and amplifies perturbations with frequencies near ω _c . This selective amplification results from the coupling between the natural tendency of velocity perturbations to grow in a stratified atmosphere and from the line force dependence on the velocity gradient, per the Castor–Abbott–Klein line-driven wind theory. We also found that the variability stems from self-excitation that occurs in the exponential atmosphere due to the nonlinearity introduced by the absolute value of the velocity gradient in the line force prescription. We conclude that self-consistently calculating ionization is insufficient for modeling the dynamics in the subsonic atmosphere. Instead, future wind or unified models should relax the Sobolev approximation, or model the radiative transfer to properly capture the resulting radiation-induced instabilities and dynamics at the wind base.